What Is the Future of AI in Pharmaceutical Manufacturing? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The pharmaceutical industry is on the verge of a transformative era with the integration of artificial intelligence (AI). Traditionally lengthy and costly dr...
Keywords: Drug Discovery and Pharmaceutical AI; Future; Pharmaceutical; Manufacturing; Artificial Intelligence; Machine Learning; Deep Learning